Recepção e rearticulação de discursos em contextos turísticos em formação. - Travé-Molero, Raul (Universidad Nacional del Litoral, 2021)
The (diachronic) case study of Portmán (Region of Murcia, Spain), with its history of environmental degradation and social struggle, widely covered by the regional press, allows us to rethink the studies of communicative reception and analyse the processes of rearticulation and discursive appropriation pointing out the importance of the historical and social conditions of the reception processes. These processes are intrinsically related to local cultural matrixes and significant mediations present in the territory. These, in turn, cannot be understood without the socio-economic changes that the town has undergone since the mid-twentieth century to the present.